Multifocal mixed testicular cancer with osteoblastic bone metastases: a case report - Alvarez-Gomez , Keily; Campanería-Hernández , Jean Marcos; Vinageras-Hidalgo, Carlos Luis; Méndez-Fiallo , José Antonio (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2026)
Introduction: Testicular cancer is the most common neoplasm in men aged 15 to 35. Mixed germ cell tumors account for up to 60% of non-seminomatous cases. Bone dissemination is exceptional (3–9%), and osteoblastic metastases are extremely rare, associated almost exclusively with predominant choriocarcinoma. Objective: To describe a rare case of multifocal mixed testicular cancer with osteoblastic bone metastases. Case Presentation: A 46-year-old male patient presented with a 1 cm, hard, painless mass in the left testicle, present for 3 months. Tumor markers showed normal alpha-fetoprotein levels (1.53 IU/mL) and elevated β-hCG levels (13.4 IU/mL). Doppler ultrasound revealed a heterogeneous, hypervascularized mass measuring 10 × 8 mm. Computed tomography with bone window settings revealed osteoblastic lesions in the thoracic spine and the left femoral head. A left inguinal orchiectomy was performed. Histological analysis reported a mixed germ cell tumor consisting of seminoma (50%), embryonal carcinoma (25%), yolk sac tumor (15%), and choriocarcinoma (10%), with lymphovascular invasion. Conclusions: Mixed testicular cancer containing choriocarcinoma (10%) may present with osteoblastic bone metastases—an exceptional finding that justifies the use of bone window settings during staging. Normal alpha-fetoprotein levels do not rule out metastatic disease when β-hCG levels are elevated. Reporting such atypical presentations enhances clinical suspicion in patients falling outside the classic age range for this disease.